Nigerian groundnut exports : origins and early development - Hogendorn, Jan S. (Zaria : Ahmadu Bello University Press, 1978)
The book examines the campaign for cotton, the effects of the railway's arrival, the shift into groundnut buying by large numbers of traders previously engaged in the kola nut trade. It also enumerate the strategies used to increase groundnut production, and the ultimate defeat of cotton.
Includes index.
Bibliography: p. [155]-167.
usc 28/01/2019
Loans
Keywords: Peanut industry; Cotton trade; Hausa (African people); Nigeria, Northern